EFEKTIVITAS MEDIA ROULETTE BERSUARA DALAM PENGENALAN KOSA KATA BAHASA INGGRIS TERHADAP ANAK USIA DINI TAMAN KANAK- KANAK BAITURRIDHA 2 LUBUK BUAYA - Azura Febrian Sulma, Elise Muryanti; Rismareni Pransiska, Tisna Syafnita (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
English language introduction to early childhood needs to be stimulated with simple basic knowledge so that it is easily understood by children. The increasingly rapid development of science and technology requires the next generation of the nation to compete both at the national and global levels, which is required to have English language skills. This makes English language introduction to early childhood important to children. Many children who experience assistance in learning English vocabulary at Baiturridha 2 Lubuk Buaya Kindergarten have not developed according to their age, as well as the lack of children's involvement in learning English using picture media. This problem shows that the introduction of English vocabulary in learning needs to be designed to be more interesting and effective for children. The type of research used is quantitative research with an experimental method. The population in this study amounted to 15 children. The research design used a one group design with a purposive sampling technique, namely sampling based on certain considerations needed for the study. Hypothesis testing in this study used a Paired Sample T-test with a significance level of 0.05. The results of this study indicate that the use of audio roulette media has an effect on introducing English vocabulary to early childhood students at Baiturridha 2 Kindergarten, Lubuk Buaya. This is evidenced by the improvement in learning outcomes seen from the pre-test and post-test scores. Furthermore, the sig value (2-tailed) is 0.000.